Tumour measurements on imaging for clinical trial: A national picture of service provision - Georgina Hopkinson; Jonathan Taylor; Jonathan Wadsley; Angela Darekar; Christina Messiou; Dow-Mu Koh (BJC Reports)
Abstract Background Radiological response evaluation metrics such as RECIST 1.1 inform critical endpoints in oncology trials. The UK was the 6th highest recruiter into oncology trials worldwide between 1999 and 2022, with almost 9000 oncology trials registered during the same period. However, the provision of tumour measurements for oncology trials is often ad hoc and patchy across the NHS. The aim of this work was to understand the barriers to providing an effective imaging tumour measurement service, gain insight into service delivery models and consider the successes and challenges from the perspective of both service providers and end users. Methods An electronic survey was distributed to those who provide tumour measurement response review for clinical trials (service providers) and those that request and use such measurements in trial activities (service users). Results Responses from 35 sites demonstrated substantial variation in service provision across the UK. Despite workforce pressures, service is largely delivered through radiologists with a minority utilising radiographer role extension. Only 20% of the service providers had dedicated training and 29% received robust financial reimbursement. Discussion Service variation is likely a consequence of limited training, education and infrastructure to support robust service, compounded by increasing radiology workload and workforce pressures.